Radiation therapy technologists' involvement and opinion in research: A national survey in Italy. (September 2020) - Piro, D.; Boldrini, L.; Cornacchione, P.; Votta, C.; Bianchi, M.; Balducci, M.; Gambacorta, M.A.; Valentini, V.; Pasini, D.
Highlights: The engagement of Italian RTTs in clinical research is not homogeneous. An active integration of RTTs in research pipelines may enhance RT research quality. Italian RTTs are willing to be integrated into multidisciplinary research projects. Abstract: Introduction: This survey describes Italian RTTs' involvement and opinions in research activities related to radiation oncology. Primary aim was to assess the degree of involvement of the national RTTs community in research and to describe how RTTs can integrate their skills collaborating with other professionals. Materials and methods: A ten-items multiple-choice questionnaire, with 2–8 possible responses, was developed by a steering committee and generated on a survey platform. Links were sent via email to Italian RTTs. The questions were divided in 3 domains: demographic data; scientific research and activity; opinions about RTTs role in scientific research. The survey started on October 1, 2018 and ended on January 31, 2019. Results: One hundred thirty-five out of 509 (26.5%) RTTs responded to the questionnaire at its expiring date; 97.73% think to be valid contributors in radiation oncology research, expressing clear interest in "data collection" tasks (52.71%); 38.64% feel unsupported by other professionals in the research team and 59.85% of the respondents are not members in any scientific society. Conclusions: The role of Italian RTTs in research is heterogeneous. Mainly RTTs in the age range from 30 to 40 years responded to the survey showing their interest in scientific research. This might be related to different informatics and educational skills as well as to personal attitudes. RTTs particular skills, like data management and technical hypothesis generation abilities, are of benefit to realize research projects. Therefore, engaging RTTs in research activities is strongly suggested.